Postural Balance Parameters as Objective Surgical Assessments in Low Back Disorders: A Systematic Review - Yen, Tzu Chuan (J Appl Biomech, 2015)
BACKGROUND: Postural balance assessments could render useful objective performance measures to evaluate the efficacy of low back disorder surgeries. Several studies utilized balance parameters but have not yet been collectively examined to determine an overall effect. Therefore, the purpose of the review is to investigate these measurements and determine their sensitivity for disparate spinal disorders after surgical intervention. METHODS: Articles were selected based on the following: 1) sample consisted of low back disorder individuals who underwent surgery; and 2) balance measurements were obtained both pre-surgery and at least at one time point post-surgery. Delphi consensus helped evaluate article quality and effect sizes were also determined for some studies. FINDINGS: Most of the articles addressed two specific low back disorders: 1) adolescent idiopathic scoliosis/spinal fusion; and 2) disc herniation/decompression surgery. For scoliosis patients, body sway seemed to increase (14–97%) immediately following surgery but gradually reduced (1–33%) approaching the one year post-spinal fusion assessment. For disc herniation patients, sway range, sway velocity, sway area, and sway variability all decreased (19–42%) immediately post-surgery. INTERPRETATION: Balance assessments for adolescent idiopathic scoliosis patients who underwent surgical intervention should be performed with visual occlusion, focus on time domain parameters, and evaluated with longer follow-up times. Disc herniation patients who underwent decompression surgery should also have balance assessments with visual deprivation, test conditions specifically addressing hip strategy, and correlation with the pain level.